Operation Control of In Situ Combustion Based on the Material Balance Equation - Haiyan Jiang; Shibao Yuan; Lehong Li; Jiao Wang; Hao Wang; Tianyue Li (Geofluids)
The stability of combustion in the process of fire flooding requires not only a reasonable gas injection rate but also a matching exhaust rate. A reasonable injection-production balance system is very important. Based on the material balance of injection-production, the expression of injection-production ratio suitable for normal fire flooding production is established. The air injection rate of fire flooding combustion and oxygen consumption of formation pressurization is analyzed by this formula to calculate the gas production and liquid production in combustion. The reasonable injection and production parameters for the oilfield are calculated by using the oilfield parameters. It can be seen that the calculated value of injection-production ratio is consistent with the actual value, which shows that the injection-production ratio is reasonable and can guide the adjustment of production parameters in the oilfield.